Discussion - Of Mr. Malcolmson's Paper on The Sierra Mojada, Coahuila, Mexico, and Its Ore-Deposits (see p. 100) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1902)
S. F. Emmons, Washington, D. C.: Mr. Malcolmson's paper on the intensely interesting deposits of the Sierra Mojada creates a strong desire to visit the region so well described. Although it is difficult to intelligently discuss a locality that one has never seen, I cannot refrain from offering some remarks in the nature of a tentative suggestion: 1. Age of Beds.—Mr. Malcolmson speaks of the enormous thickness of limestone forming the Sierra Mojada as belonging to the Carboniferous series. If this is not a typographical error, it seems that he should present some evidence for such age, for Chism,* in his previous article on the district, says the only fossils found there were said to be Cretaceous; and it is well known by the investigations of R. T. Hill and others that the great thickness of limestone in this part of Mexico is of Cretaceous age. 2. Structure of Mountains.—Mr. Malcolmson presents good reasons for thinking that the structure of the two related mountain masses (Sierra Mojada and Sierra Planchada) is not the simple anticlinal fold given by Mr. Chism's section, it being evident that there has been faulting as well as flexure. I venture to add that the facts presented by Mr. Malcolmson seem to suggest the possibility that, instead of being simply an eroded anticline, the valley between the two ranges may have been formed, in part at least, by the irregular faulting down of the intermediate block, on the surface of which the volcanic breccia had originally accumulated at a higher level. The sections of the Exploradora and the San Josh mines, in the smooth surface of the contact, with clay selvages and the occasional slickensides, certainly suggest a structural fault between the limestone and breccia. The arrangement of some of the